New British Fashion Photography: Going Against the Conventionally Beautiful - Julie Morère (Études Britanniques Contemporaines, 2015)
The theoretical framework around British fashion photography has often considered it as a mercantile (Hall-Duncan) and social issue rather than an artistic one (Val Williams). Not only considering fashion photography as a visual archiving of British style in a cultural continuum woven through British art, music, films and design, this paper will observe how contemporary fashion photographers, editors, stylists and set designers chronicle the spirit of the times, but also offer to the viewer the product of their combined imaginations mediated by the fashion industry. Challenging the assertion of Britishness in the face of the multiplicity of its expressions in a fast-changing, globalized era, fashion photography may resort to the vernacular and the documentary to fabricate the new. Shaping our memories and the way we look at a picture, contemporary fashion images reflect their own impermanence and incredible vitality, questioning the British identity and the very notion of globalization.